A cointegration analysis of agricultural, energy and bio-fuel spot, and futures prices. Issue 7 (7th February 2018) - Allen, David E.; Chang, Chialin; McAleer, Michael; Singh, Abhay K
Abstract : This article features an analysis of the cointegration relationships among agricultural commodity, ethanol and Cushing crude oil spot, and future prices. The use of grains for the creation of bio-fuels has sparked fears that these demands are inflating food prices. We analyse approximately 10 years of daily spot and futures prices for corn, wheat, sugar ethanol, and oil prices from Datastream for the period 19 July 2006 to 2 July 2015. The analysis features Engle-Granger pairwise cointegration and partial cointegration. Pairs of series, that are cointegrated, are analysed using Markov-switching VECM and Impulse Response Analysis, which confirms that these markets have significant linkages that vary according to whether they are in low or high volatility regimes.